A qualitative analysis of the perceived determinants of success in elite esports athletes - Poulus, D. R.; Coulter, T. J.; Trotter, M. G.; Polman, R. (Journal of Sports Sciences, 2022)
The current study aimed to qualitatively investigate the perceived determinants of success in professional esports athletes. Guided by the bioecological model (Bronfenbrenner & Morris, 2006), thematic analysis was used to explore elite esports athletes` perceptions of success determinants. Semi-structured interviews were conducted with seven elite esports athletes. The interviews were used to investigate players` psychology when playing well, training in elite esports, and working in esports teams. Deductive and inductive analyses were conducted to capture the core themes of success in esports within the bioecological model. When playing well, elite esports athletes experienced high levels of confidence, uninterrupted focus, and flow states. Elite esport athletes use mental strategies to help regulate their emotions and remain mindful in the presence of "tilt". Furthermore, breathing techniques and tactical breaks were used when players felt nervous or when trying to "reset" from a stressful situation. When working in elite esport teams, players reported using strategies to improve team cohesion and that the biggest challenge was interpersonal disagreements. The results contribute to the growing body of literature highlighting the psychological similarities between elite esports and traditional sports athletes and serve as an index for future research into high-performance in esports.